THE EFFECTIVENESS ONLINE LEARNING MEDIUM IN INCREASING VOCATIONAL EDUCATION STUDENT MOTIVATION - nFn Sutirman; nFn Yuliansah; Muslikhah Dwihartanti (Balai Besar Guru Penggerak Jawa Timur, 2022)
The industrial era 4.0 demands changes in various aspects of life, including using the learning strategies and media. A learning strategy that suits the demands of the industrial era 4.0 is online learning using digital information technology-based. Many platforms offered to teachers for online learning, both paid and free platforms. Google Classroom is an example of a free online learning platform. Meanwhile, Office Administration Vocational School teacher usualy conduct offline learning using PowerPoint. This study aimed to find out the effectiveness of learning media of Google Classroom and PowerPoint in increasing the learning motivation of students in Office Administration Vocational School (OAVS) in the Special Region of Yogyakarta. This study used a quantitative approach, a quasi-experimental method, and a non-equivalent control group design model. The population was students of OAVS in the Special Region of Yogyakarta, covering four districts and one city. The sample was selected by cluster sampling technique based on the districts or city. Each district or city selected two schools as a sample, in which homogenous in characteristics. Data collection techniques used observation, documentation, and focus group discussion.AbstrakEra industri 4.0 menuntut perubahan dalam berbagai aspek kehidupan, termasuk penggunaan strategi dan media pembelajaran. Strategi pembelajaran yang sesuai dengan tuntutan era industri 4.0 adalah pembelajaran online menggunakan berbasis teknologi informasi digital. Banyak platform yang ditawarkan kepada guru untuk pembelajaran online, baik platform berbayar maupun gratis. Google Classroom adalah contoh platform pembelajaran online gratis. Sedangkan guru SMK Administrasi Perkantoran biasanya melakukan pembelajaran offline dengan menggunakan PowerPoint. Penelitian ini bertujuan untuk mengetahui keefektifan media pembelajaran Google Classroom dan PowerPoint dalam meningkatkan motivasi belajar siswa SMK Administrasi Perkantoran di Daerah Istimewa Yogyakarta. Penelitian ini menggunakan pendekatan kuantitatif, metode eksperimen semu, dan model desain kelompok kontrol non-ekuivalen. Populasi dalam penelitian ini adalah siswa SMK Administrasi Perkantoran di Daerah Istimewa Yogyakarta yang meliputi empat kabupaten dan satu kota. Sampel dipilih dengan teknik cluster sampling berdasarkan kabupaten atau kota. Setiap kabupaten atau kota memilih dua sekolah sebagai sampel yang sifatnya homogen. Teknik pengumpulan data menggunakan observasi, dokumentasi, dan focus group discussion.